HRM Practices, Human Capital, Individual Performance, and Organizational Performance: An Empirical Evidence from Indonesian SMEs - Jonner Simarmata (Greenation International Journal of Tourism and Management, 2023)
This study aims to prove whether or not human capital and employee performance mediate the relationship between HRM practices and organizational performance in the context of SMEs. For this purpose, a set of questionnaires were distributed to 300 respondents consisting of 40 batik SME owners and 260 employees. The collected data were analyzed by using the PLS-SEM method. The findings show that human capital and individual performance positively and significantly mediate the relationship between HRM practices and organizational performance. Hence, it is suggested for batik SME owners/managers implement HRM practices that effectively improve human capital and employee performance.